2023
DOI: 10.4103/njcp.njcp_401_22
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spinal Anesthesia that is Performed in Sitting or Right Lateral Position on Post-Spinal Headache and Intraocular Pressure During Elective Cesarean Section

Abstract: Background: Although spinal anesthesia can be applied in different patient positions, the most frequently used positions are sitting and lateral positions. It is known that different patient positions during spinal anesthesia have effects on hemodynamic parameters, postdural puncture headache, and intraocular pressure. Aim: The study aimed to determine the effect of spinal anesthesia performed in either sitting or right lateral position on postspinal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…They asserted that in sitting position group, 9.8% (5 women) and in lateral position group, only 1.9% (1 woman) had post dural puncture headache. 22 Our study further disclosed that among 20 women of sitting position group who had PDPH, 6.7% (4 women), 10.0% (6 women), 8.3% (5 women), 5.0% (3 women) and 3.3% (2 women) had day of onset 1, 2, 3, 4 and 5, respectively. However, among 4 women of lateral position group who had PDPH, 5.0% (3 women) had day of onset 1 and only 1.7% (1 woman) had day of onset 4.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…They asserted that in sitting position group, 9.8% (5 women) and in lateral position group, only 1.9% (1 woman) had post dural puncture headache. 22 Our study further disclosed that among 20 women of sitting position group who had PDPH, 6.7% (4 women), 10.0% (6 women), 8.3% (5 women), 5.0% (3 women) and 3.3% (2 women) had day of onset 1, 2, 3, 4 and 5, respectively. However, among 4 women of lateral position group who had PDPH, 5.0% (3 women) had day of onset 1 and only 1.7% (1 woman) had day of onset 4.…”
Section: Discussionsupporting
confidence: 64%
“…Our findings are supported by a number of studies which showed a statistically significant and lower incidence of PDPH in lateral position as compared to sitting position. 2,6,21,22 The results of a similar study performed by Hussain et al showed that 20.0% (9 women) in sitting position group while only 4.4% (2 women) in lateral position group had post dural puncture headache. 2 Similarly, the results of another study conducted by Demilew et al also corroborated that later position is better than sitting position with regards to post dural puncture headache.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…For lower extremity surgery, if there are no contraindications, we usually have the option of spinal block or nerve block anesthesia to complete the procedure. Spinal block and nerve block anesthesia require postural placement [7,8], and this patient was unable to cooperate with postural placement due to trauma and obesity from multiple fractures throughout the body. The patient had a large area of trauma to the left leg, and simple nerve block anesthesia was not adequate.…”
Section: Discussionmentioning
confidence: 99%